2014
DOI: 10.4103/0301-4738.128618
|View full text |Cite
|
Sign up to set email alerts
|

Brachytherapy of intra ocular tumors using ′BARC I-125 Ocu-Prosta seeds′: An Indian experience

Abstract: Aim:To report our experience of brachytherapy using ‘BARC I-125 Ocu-Prosta seeds’ for the management of intraocular tumors with regard to tumor control, globe preservation visual outcome, and patient survival at Sankara Nethralaya, Chennai, India between September 2003 and May 2011.Materials and Methods:We reviewed records of 35 eyes of 35 patients who underwent ophthalmic brachytherapy between September 2003 and May 2011. Twenty-one cases had choroidal melanoma, nine had childhood retinoblastoma, two had adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In India, majority of the melanomas are enucleated by the ophthalmologist and a small fraction of the patients who are treated at tertiary referral eye centre also have opportunity for plaque therapy [ 17 ]. Currently, much emphasis is laid on the largest tumor diameter (LTD) and a few centres do offer in-situ hybridisation (CISH) based M3 detection [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In India, majority of the melanomas are enucleated by the ophthalmologist and a small fraction of the patients who are treated at tertiary referral eye centre also have opportunity for plaque therapy [ 17 ]. Currently, much emphasis is laid on the largest tumor diameter (LTD) and a few centres do offer in-situ hybridisation (CISH) based M3 detection [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Another study from India on medium-sized melanomas <6 mm in height showed a globe salvage rate of 74% with Ocuprosta seeds. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…The melanomas treated by them were medium-sized tumors that required lesser mean radiation dosage. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 13 14 ] Very few reports about the alternative treatment options available in India exist in the literature. [ 9 15 ] There are no studies from India comparing these two treatment modalities for choroidal melanoma, due to the low incidence of this disease. This is the first study comparing long-term survival after brachytherapy and enucleation for choroidal melanomas in the Asian Indian population.…”
Section: Discussionmentioning
confidence: 99%